Influence of demographic characteristics on dining out and food ordering behaviour among older persons - A. Z. A., Bakar; L., Ganesan; Haron, Sharifah A.; Haron, Sharifah A.; F. A. C., Ishak (Human Resource Management Academic Research Society, 2024)
Malaysia is a developing multicultural nation that is experiencing population aging with an estimated seven percent of the population made up of individuals aged 65 and above in 2020. The diverse cultures as well as the growing older persons population makes Malaysia an interesting population to be studied; however, the stereotypes held about older persons (limited spending power and frail) have prevented marketers from giving the rightful focus on this growing market segment. Food consumption trend is different among age groups, and little is known about the restaurant choice behaviour among older persons in Malaysia. This study explored demographic characteristics that influence older persons restaurant visiting and ordering behaviour. Through qualitative approach, 15 informants aged 55 and above were purposively sampled from Klang Valley. Semi-structured interviews were conducted and recorded; then transcribed, translated, content analysed and coded into themes. The results of this study revealed that the demographic characteristics that influenced dining out behaviour were education level, income and employment status, and culture and religion. Surprisingly, those with higher education level were more empathetic and tolerant towards low-skilled foreign workers. Additionally, they preferred the indoor comforts of clean air and air conditioning of the foodservice establishment; whereas their counterparts preferred the natural and spacious environment of outdoor dining. This study revealed some insights on the demographic characteristics that influenced older consumers dining out and ordering behaviour in Klang Valley; in the hope to initiate restaurateurs to better consider the new roles of older people as consumers in Malaysia to better meet their needs and expectations.